Changes of working capital management and firm value in Thailand and Singapore - Zariyawati, Mohd Ashhari; Mohammad Reyad, Hossain (Inderscience Publishers, 2022)
Efficient working capital management ensures a firm can run the day-to-day operation smoothly to sustain in a longer period. Hence, the firm should be more careful on changes of working capital management. The study explores the impact of changes of working capital management on firm value using 200 listed non-financial firms from Thailand and Singapore from 2009 to 2018. By employing static panel data regressions, the study demonstrates that shareholders in Thailand perceive an extra working capital investment is significantly less worth than an extra Thai baht of cash investment. Conversely, shareholders in Singapore perceive that extra Singapore dollar of cash investment and extra working capital investment reduces firm value. These different results from both countries are expected due to the different levels of market development.